2015
DOI: 10.1016/j.jhep.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic PTEN deficiency improves muscle insulin sensitivity and decreases adiposity in mice

Abstract: Background & Aims: PTEN is a dual lipid/protein phosphatase, downregulated in steatotic livers with obesity or HCV infection. Liver-specific PTEN knockout (LPTEN KO) mice develop steatosis, inflammation/fibrosis and hepatocellular carcinoma with aging, but surprisingly also enhanced glucose tolerance. This study aimed at understanding the mechanisms by which hepatic PTEN deficiency improves glucose tolerance, while promoting fatty liver diseases. Methods: Control and LPTEN KO mice underwent glucose/pyruvate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 34 publications
8
69
0
Order By: Relevance
“…It is of note that all mouse models exhibiting a dissociation between hepatic steatosis and insulin resistance are characterised by an increase in hepatic FGF21 levels and MUFA/SFA ratio, and are never associated with an increase in HGP [2,3,6]. The latter observation reinforces the key role of increased HGP in the appearance of fasting hyperglycaemia …”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…It is of note that all mouse models exhibiting a dissociation between hepatic steatosis and insulin resistance are characterised by an increase in hepatic FGF21 levels and MUFA/SFA ratio, and are never associated with an increase in HGP [2,3,6]. The latter observation reinforces the key role of increased HGP in the appearance of fasting hyperglycaemia …”
Section: Discussionmentioning
confidence: 70%
“…However, recent studies have demonstrated that triacylglycerol accumulation in the liver can be associated with improved insulin sensitivity, due to better glucose control in the peripheral tissues [2,3,6,24,25]. To further document the mechanisms involved in this interorgan communication, we studied whether liver metabolism might control insulin signalling in the peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the inhibition of these pathways in turn leads to the appearance of beige adipocytes. This includes peripheral serotonin levels (Crane et al 2015), the TGFb/SMAD3/myostatin cascade (Shan et al 2013, hepatic PTEN (Peyrou et al 2015), Notch or prolactin receptor signaling (Auffret et al 2012, Bi et al 2014, as well as Cox2 (Madsen et al 2010).…”
Section: Ways Of Browningmentioning
confidence: 99%